Musicianship in the digital age - Edstrom, Brent (Thomson Course Technology, 2006)
Unlike many other books on the market, "Musicianship in the Digital Age" effectively combines music technology with musicianship. The book provides technical instruction on topics such a sequencing, synthesis, loop-based tools, and editing, with insights on how to actually use that technology to sequence and record original compositions. Organized into three parts, the first two parts cover the technological and theoretical aspects of music production while the third part ties together all of the skills learned by presenting fifteen demonstration scores and recordings with a detailed description of the entire production process. Each chapter also features helpful tips and suggested activities that, along with the companion CD, help solidify the skills learned. Readers will learn many musical concepts that will enhance the creative process and foster a versatile approach to sequencing and composition